Microstructure evolution and anisotropy of nickel-based superalloy fabricated by LPBF - Mingchuan LI; Rui MA; Shuai CHANG; Qishun WANG; Liqun LI (Hanjie xuebao, 2025)
The microstructure evolution and anisotropy mechanism of IN738LC alloy under varying scanning speeds in laser powder bed fusion (LPBF) were investigated. Optical microscopy (OM) and scanning electron microscopy (SEM) were used to characterize the microstructural features, X-ray diffraction (XRD) was employed to examine the texture, and a microhardness tester was used to evaluate microhardness and anisotropy. The results showed that as the scanning speed increased from 800 mm/s to 1600 mm/s, the grain size became significantly smaller. At low scanning speeds, the grain major axis was preferentially aligned along the build direction. However, at high scanning speeds, the grain major axis transitioned to being aligned normal to the melt pool boundary. This was attributed to the higher melt pool remelting rate at low scanning speeds, which promoted more preferential epitaxial growth of dendrites along the build direction. This strong preferential growth along the build direction also resulted in a (200) texture along the build direction. The intensity of this texture decreased as the scanning speed increased. Furthermore, the (200) preferential alignment along the build direction led to an increased presence of soft axes in the horizontal section, resulting in anisotropy where the horizontal microhardness was lower than that of the side section.